Re-souling spirituality redefining the spiritual dimension in schools - Plater, Mark (2017)
This article argues that our present model for defining spiritual development within the English school context unhelpfully lends itself to a binary of spirit-body, evoking potential distracting questions about whether or not the soul/spirit actually exists as a separate entity from the body, a question more specifically suited to the religious education curriculum. Instead, using an interdisciplinary approach, the author argues for an alternative model of spirit-soul, based on definitions taken from the contemporary Wholeness movement, in which spirit is perceived as that in us which seeks vision and transcendence, and soul as that which seeks engagement, depth and rootedness. Although the model provides us with an alternative binary, no duality is intended. Rather, the argument is that personal and community maturity implies balance and wholeness of body, soul and spirit, which is more clearly exemplified within this proposed new conceptualisation.
Keywords: Spirit; Educational models; Soul; soulfulness; Spiritual Development; Spirituality; Wholeness